"Y"-shape armed amphiphilic star-like copolymers: design, synthesis and dual-responsive unimolecular micelle formation for controlled drug delivery. Issue 36 (23rd August 2017) - Fan, Xiaoshan; Wang, Xiaoyuan; Cao, Mengya; Wang, Chenguang; Hu, Zhiguo; Wu, Yun-Long; Li, Zibiao; Loh, Xian Jun
Abstract : Dual stimuli-responsive unimolecular micelles from "Y"-shape armed amphiphilic star-like copolymer are designed for controlled drug delivery. Abstract : In this study, a novel amphiphilic star-like CD-PCL-SS-PEG(PNIPAM) copolymer with a disulfide linkage at the junction points of the "Y"-shaped arms is designed and further fabricated into dual temperature and redox-responsive unimolecular micelles for controlled drug delivery in cancer therapy. During the synthesis, the end-alkyne functionalized hydrophobic star-like core CD-PCL-SS-alkyne was first synthesized by ring-opening polymerization (ROP) of ε-CL using β-CD as an initiator, followed by a two-step end group transformation reaction. Then, CD-PCL-SS-alkyne was coupled with α, α′-azide, hydroxyl-PEG (PEG-N3 (OH)) via "click" chemistry to obtain PCL-SS-(OH)PEG copolymers with reactive –OH at the junction point. Furthermore, esterification between the –OH on PCL-SS-(OH)PEG and S -1-dodecyl- S ′-(α, α′-dimethyl-α′′-acetic acid)trithiocarbonate (DDAT) was carried out to afford the CD-PCL- b -(CTA)PEG copolymer, followed by reversible addition–fragmentation chain-transfer polymerization (RAFT) of N -isopropylacrylamide to obtain the desired star-like CD-PCL-SS-PEG(PNIPAM) copolymer. The targeted copolymer and its intermediates were characterized by 1 H NMR and gel permeation chromatography (GPC). The unimolecular micelles formed from the CD-PCL-SS-PEG(PNIPAM) copolymer were studied by dynamic light scattering (DLS) and transmission electron microscopy (TEM) techniques. Drug release studies from CD-PCL-SS-PEG(PNIPAM) micelles exhibited sustained release profiles and the rate of release can be tuned by variation of temperature and glutathione (GSH). Cellular uptake and in vitro stimuli-mediated intracellular DOX release were investigated by flow cytometry and confocal laser scanning microscopy (CLSM) measurements, demonstrating high cellular uptake efficiency and significant intracellular drug release from doxorubicin (DOX) loaded CD-PCL-SS-PEG(PNIPAM) micelles via controlling temperature and reduction. Together with the excellent cell biocompatibility, the new star-like CD-PCL-SS-PEG(PNIPAM) copolymer reported in this paper could potentially be used as intelligent nanocarriers for controlled drug delivery.